Welfare Impacts of Genetic Testing in Health Insurance Markets: Will Cross-Subsidies Survive? (2019)
Personalized medicine is still in its infancy, with costly genetic tests providing Little actionable information in terms of e¢ cient prevention decisions. As a consequence, few people undertake these tests currently, and health insurance contracts pool all agents irrespective of their genetic background. Cheaper and especially more informative tests will induce more people to undertake these tests and will impact not only the pricing but also the type of health insurance contracts. We develop a setting with endogenous prevention decisions and we study which contract type (pooling or separating) emerges at equilibrium as a function of the proportion of agents undertaking the genetic test as well as of the informativeness of this test. Our results show that, ceteris paribus, the higher is the proportion of tested agents, the more likely is the emergence of a separating equilibrium that implies some risk discrimination. However, a better pooling contract in which policyholders undertake preventive actions (and lower their health risk) can be attained if the informativeness of the genetic tests increases su¢ ciently. Once the proportion of tested individuals reaches a threshold, we move abruptly from pooling to separating equilibrium, which unambiguously decreases social welfare. Once the equilibrium is of the separating type, social welfare increases with the genetic tests take-up rate, thanks to a composition e¤ect.